Satalitic Magnetospheric Catalyzation - Ward, Jessie (JOURNAL OF ADVANCES IN PHYSICS, 2017)
This theory states that in crossing between the Earth and the Sun (non-eclipse), charged molecules absorb the Solar Magnetic Field, creating an oscillation in its intensity that pushes Electrons in the core of our planet, producing a Magnetosphere.